Planar refraction and lensing of highly confined polaritons in anisotropic media - J. Duan (Nature Portfolio, 2021)
Refraction between anisotropic media is still an unexplored phenomenon. Here, the authors investigate the propagation of hyperbolic phonon polaritons traversing α-MoO3 nanoprisms, showing a bending-free refraction effect and sub-diffractional focusing with foci size as small as 1/50 of the light wavelength in free space.